2003
DOI: 10.1001/jama.289.14.1833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Internet Behavioral Counseling on Weight Loss in Adults at Risk for Type 2 Diabetes

Abstract: Objective To compare the effects of an Internet weight loss program alone vs with the addition of behavioral counseling via e-mail provided for 1 year to individuals at risk of type 2 diabetes.Design, Setting, and Participants A single-center randomized controlled trial conducted from September 2001 to September 2002 in Providence, RI, of 92 overweight adults whose mean (SD) age was 48.5 (9.4) years and body mass index, 33.1 (3.8).Interventions Participants were randomized to a basic Internet (n=46) or to an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
589
6
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 617 publications
(632 citation statements)
references
References 20 publications
26
589
6
11
Order By: Relevance
“…All quality assessments can be found in Supplementary material Table S1. Selective reporting was the only criterion to receive high risk of bias scores for four of the studies 22, 30, 31, 32. Three studies provided monetary incentives for the completion of assessments that may have acted as a co‐intervention in respect of retention rates 22, 33, 34.…”
Section: Resultsmentioning
confidence: 99%
“…All quality assessments can be found in Supplementary material Table S1. Selective reporting was the only criterion to receive high risk of bias scores for four of the studies 22, 30, 31, 32. Three studies provided monetary incentives for the completion of assessments that may have acted as a co‐intervention in respect of retention rates 22, 33, 34.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of this study, as well as other weight-loss trials, 32 is the small representation of male participants. This limitation may be the result of this being a study testing a vegetarian diet, or as previously reported data suggest, it may be due to the fact that a lower percentage of men than women are trying to lose weight.…”
Section: Discussionmentioning
confidence: 95%
“…We found that a greater proportion of women were interested in reading about other women's progress via their tweets (83 %) than were interested in tweeting about their own progress (71 %). Despite evidence that engagement is strongly related to outcomes [35][36][37][38][39][40], waning use is common in web-based behavioral interventions [41]. More frequent engagement in an online social network for weight loss is associated with better outcomes [22].…”
Section: Original Researchmentioning
confidence: 99%